Introduction to family processes - Day, Randal (New Jersey: Lawerence Erlbaum Associates, 2003)
Contents: Introduction to family processes. Foundational family processes. Expressive family processes. Change, turbulence, and strength
Incluye bibliografía Includes bibliographical references and index
Keywords: Family - Research